Graphene surface structure in aqueous media: Evidence for an air-bubble layer and ion adsorption. (March 2019) - Zhou, Liangzhi; Islas, Luisa; Taylor, Nicholas; Bikondoa, Oier; Robles, Eric; Briscoe, Wuge H.
Abstract: Understanding graphene surface structure in aqueous media is essential for its biotechnological applications. Here, using synchrotron X-ray reflectivity (energy 14 keV), AFM imaging, and contact angle measurements, we have investigated the surface structure of CVD graphene on SiO2 /Si in water and phosphate buffered saline (PBS) at 25–60 °C. We found a diffuse layer immediately adjacent to graphene with a scattering length density (SLD) of 6.72 × 10 −6 Å −2, attributed to the presence of air bubbles on graphene under water. AFM imaging was indicative of interfacial inhomogeneity, but did not provide conclusive topography information on the bubble-covered graphene-water interface. The diffuse layer diminished after the graphene was submerged in water for 24 h at 25 °C. This is also evident from its enhanced wettability, with the water contact angle on graphene decreasing from 84.9 ± 0.4° to 55.6 ± 0.4° after submergence. An additional layer atop graphene appeared after soaking, with a thickness 10.1 Å, and a higher SLD of 19.5 × 10 −6 Å −2 at 25 °C, which increased to 11.8 Å and 21.8 × 10 −6 Å −2 at 60 °C in PBS, respectively. We discuss this observation in terms of ion mobility, possible formation of a silanol layer on the SiO2 substrate, and water structure disruption at higher temperatures. Graphical abstract: